Depression Mediates the Association Between Childhood Emotional Abuse and the Onset of Type 2 Diabetes: Findings From German Multi-Cohort Prospective Studies - Atasoy, Seryan; Johar, Hamimatunnisa; Fleischer, Toni; Beutel, Manfred; Binder, Harald; Braehler, Elmar; Schomerus, Georg; Zöller, Daniela; Kruse, Johannes; Ladwig, Karl-Heinz (Frontiers in Psychiatry, 2022)
Background: The dysregulation of glucose homeostasis via mental health stress is increasingly acknowledged, whereby depression independently increases the risk of the onset of type 2 diabetes by up to 60%. Contributing mental health factors starting in early life have further been considered, indicating that exposure to childhood emotional abuse is associated with both depression and an increased onset of type 2 diabetes in adulthood. However, the potential role of depression within the emotional abuse and type 2 diabetes link remains unknown. Methods: Data were derived from community-dwelling participants in southern and northeastern Germany who participants in the longitudinal KORA-F4 and SHIP-3 studies. Multivariable logistic regression analyses adjusted for lifestyle, somatic and psychological risk factors were used to investigate the association between childhood emotional abuse, assessed retrospectively by the Childhood Trauma Screener, and newly diagnosed type 2 diabetes cases were confirmed using a standard oral glucose tolerance test. The mediating role of depressive symptoms between childhood emotional abuse and type 2 diabetes was assessed by the Patient Health Questionnaire-9 and calculated by using the Sobel test for mediation. Results: A total of 2,973 (53.2% women, 46.8% men) participants with a mean age of 49.7 were included in the analyses, of whom 5.9% (7.1% women, 4.5% men) reported emotional abuse in childhood. Participants exposed to childhood emotional abuse had a 1.70 (1.12-2.56; p=.02) times higher odds of depression in the fully adjusted model than unexposed participants. During the 6.5 years follow-up period, 104 (3.5%) of participants developed type 2 diabetes. Participants who were exposed to childhood emotional abuse had a 2.56 (1.31-4.98, p=.005) times higher odds of developing type 2 diabetes than unexposed participants. This association was significantly mediated by the increased odds of depression in participants with childhood emotional abuse (Sobel Test; 1.84, p=.06; Goodman Test (1.91, p=.05). Conclusion: The current results indicate that the increased likelihood of type 2 diabetes onset in participants who were exposed to childhood emotional abuse is significantly attributed to increased depression in adulthood.